Gender and Age Differences in Mental Health Awareness: Insights from a Quantitative Study - Aashvi Patel; Sanskruti Kaneriya; Dhvanit Santoki; Mansi Thummar; Rahul Chauhan; Andino Maseleno (Greenation Publisher & Yayasan Global Research National, 2024)
This study explores the impact of social and organizational factors on mental health outcomes among 102 respondents in Ahmedabad, employing a quantitative research methodology. Utilizing a structured questionnaire administered via Google Forms, the research assesses mental health awareness, sources of information, comfort levels, and stigma. Key findings reveal significant differences in mental health awareness and comfort levels based on gender, while age shows notable effects on discussions of mental health. The results highlight the need for targeted interventions to enhance mental health support. This study bridges gaps in existing literature and provides actionable insights for policymakers and mental health practitioners. Future research should consider longitudinal and qualitative approaches to deepen understanding of these dynamics. Overall, this work underscores the importance of addressing mental health issues in a culturally sensitive manner to foster well-being.